PERLINDUNGAN HAK ANAK TERSANGKA DALAM TAHAP PENYIDIKAN PERKARA PIDANA - Indra Gunawan Simatupang; Fatin Hamamah; Maulana Kamal (Jurnal De Jure Muhammadiyah Cirebon, 2025)
This study aims to analyze: (1) the legal framework governing the protection of human rights for child suspects during the investigation process; (2) the potential forms of human rights violations that may occur against child suspects during investigations; and (3) efforts to optimize the protection of human rights for child suspects at the investigation stage. This research employs a qualitative descriptive method using normative juridical and empirical juridical approaches. The data were obtained through library research utilizing primary and secondary legal materials, which were analyzed based on legal principles and the classification of statutory provisions within the prevailing legal system. The results of the study indicate that: first, the legal framework concerning the protection of child suspects’ rights refers to the Convention on the Rights of the Child, Law No. 23 of 2002 on Child Protection, and the Law on the Juvenile Criminal Justice System (UU SPPA). Second, the forms of human rights violations still found in practice include physical and psychological violence, limited access to legal assistance, detention of children without considering age requirements or the principle of ultimum remedium, and the lack of implementation of diversion. Third, efforts to optimize the protection of child suspects’ rights during investigations include enhancing the capacity of law enforcement officers, providing child-friendly facilities, strengthening legal and psychosocial assistance, improving inter-institutional coordination, and promoting public awareness and participation. In conclusion, the protection of human rights for child suspects requires a collective commitment from all stakeholders to realize a humanistic and just legal system. Keywords: Legal Protection; Human Rights; Child Suspect; Investigation; Criminal Law